P77 Levels of psychological distress and predictors of distress in family carers of patients with cancer at end of life. (2nd September 2017) - Grande, GE; Rowland, C; Berg, B van den; Batistatou, E; Hanratty, B
Abstract : Background: Family carers provide substantial support for patients at end-of-life. It is important to understand how caregiving impacts on carers to guide appropriate interventions to improve carer wellbeing. The aims of this study were to investigate levels of psychological distress and predictors of distress during end of life care giving in a national sample of family carers of people with cancer. Methods: Four-month post-bereavement postal survey of a national census sample of relatives reporting a death from cancer 1–16th May 2015. Retrospective data collected included carer demographics, carers' psychological distress (GHQ-12), care giving hours and tasks, out of pocket expenses, support from informal and formal care, other demands on carers' time (work, other caregiving responsibilities, voluntary work), opportunities for respite, patient symptoms and activities of daily living (ADL). Exploratory univariate analyses were used to describe the data and inform multivariate analysis. Results: Surveys were completed by 1504 (28.5%) of 5271 carers. Carers' median GHQ distress score was 7 (IQR 4–9), where a score>=4 indicates 'caseness' for psychological distress. Univariate analysis results at p<0.05 indicate that increased hours of caregiving, other caring responsibilities and the patient's worsening symptoms and reduced ADL increased distress. Formal support, hours of volunteering and respite were associated with reduced distress. Carer age, sex, work situation and level of deprivation also related to distress. Multivariate analysis indicates that the total hours of care giving, patients' psychological symptoms and the carer being female was related to increased distress, whilst formal service provision was related to reduced distress. The final model explained 19% of variance in distress. Conclusion: A considerable majority of family carers suffer clinically significant levels of psychological distress during end of life care giving. Objective care burden in the form of total hours of caregiving is associated with increased distress. Being female and caring for a patient with psychological symptoms appears to increase distress, whereas support from formal care services can ameliorate distress. Whilst the final model explains a modest amount of variance in carer distress, it indicates that reduction in objective care burden and support from services can have an important, positive impact. The study was funded by Dimbleby Cancer Care; NIHR CLAHRC Greater Manchester